Falsafah Sains Ibn al-Haytham Dengan Rujukan Khas Kepada Kitāb Thamarah al-Ḥikmah: Ibn al-Haytham’s Philosophy of Science with Special Reference to Kitāb Thamarah al-Ḥikmah - Muhamad Ishaq, Usep; Wan Daud, Wan Mohd Nor (Afkar: Jurnal Akidah dan Pemikiran Islam, 2017)
Ibn al-Haytham (d. 1038/9) is hirherto known merely as a scientist and mathematician. However, his works in other fields, such as in philosophy, is unavailable. Therefore, most of studies on his thought in philosophy were based only on his scattered excerpts in works on science and mathematics, or used secondary sources and indirect references. There has been little research done so far on his only surviving work known on philosophy Kitāb Thamarah al-Ḥikmah or Maqālah ʿan Thamarah al-Ḥikmah; in fact, this work contains many philosophical aspects that are crucial to understand his thought and views on philosophy in general. The manuscript of Kitāb Thamarah al-Ḥikmah MS 1604 is held at Köprülü library Turkey and has been firstly edited in 1991. This paper introduces this work and discusses some philosophical aspects mainly on his philosophy of science, such as the purposes of studying nature, ontological, and epistemological aspects mainly on the channels of knowledge, and the framework used by Ibn al-Haytham in the study of natural phenomena. The study found that the fundamental concepts of his philosophy of science are in line with the worldview of Islām.